Comparative clinical pharmacology of mometasone furoate, fluticasone propionate and fluticasone furoate. (December 2022) - Daley-Yates, Peter T.; Deans, Amanda; Mehta, Rashmi; Sousa, Ana R.
Abstract: Aims: To investigate the pharmacokinetics and effects on the hypothalamic-pituitary-adrenal (HPA) axis of mometasone furoate (MF), fluticasone propionate (FP) and fluticasone furoate (FF). Methods: Study 1 : Fourteen healthy participants received inhaled and intravenous MF (inhaled dose via Twisthaler) and FP (inhaled dose via Diskus), both given at 400 μg, using a randomised, single-dose, four-way crossover design. Study 2: Twenty-seven participants with mild to moderate asthma, who discontinued their corticosteroid medication for 5 days to obtain a baseline 24 h serum cortisol, received inhaled MF Twisthaler and FP Diskus, both given at 400 μg twice daily (BID), using a randomised, 14-day repeat dose, two-way crossover design. Study 3: Forty-four healthy participants were randomised to a double-blind, placebo-controlled, five-period crossover study where the following treatments were administered via the inhaled route for 7 days: FP Diskus (250, 500, 1000 μg BID), FF Diskus (100, 200, 400, 800, 1600 μg once daily [QD]) or placebo Diskus. In each study, 24-h serial blood samples were collected and assayed to assess concentrations of MF, 6β-hydroxy mometasone, mometasone, FP, FF and cortisol. Pharmacokinetic and serum cortisol parameters were estimated as geometric means and 95% confidence intervals (CI). Results: Study 1 : For intravenous MF and FP, respectively: absolute bioavailability was 11.4% (95% CI: 7.5, 17.6) and 7.8% (6.3, 9.6); plasma clearance was 47 L/h (41, 52) and 60 L/h (52, 69); half-life was 7.4 h (6.9, 8.0) and 7.2 h (6.5, 8.0); and volume of distribution was 499 L (439, 567) and 623 L (557, 698). Inhalation of single dose MF or FP did not significantly affect serum cortisol (<10% reduction from baseline), whereas intravenous administration of MF or FP each changed serum cortisol by approximately −50% from baseline. Study 2 : For MF and FP, respectively: area under the curve up to the last measurable concentration on Day 1 was 421 pg h/mL (270, 659) and 248 pg h/mL (154, 400), and on Day 14 was 1092 pg h/mL (939, 1269) and 591 pg h/mL (501, 696); absolute bioavailability was 12.8% (11.2, 14.2) and 8.9% (7.7, 10.2). On Day 14, 24-h serum cortisol change from baseline was −35% (−44%, −26%) and −18% (−28%, −5%) for MF and FP, respectively; the reduction was significantly greater for MF than FP (ratio for geometric adjusted mean serum cortisol concentration: 1.28 [1.04, 1.56]). Low plasma concentrations of 6β-hydroxy mometasone were detected after intravenous dosing (Study 1 ) and after multiple inhaled dosing (Study 2 ); mometasone was not detected in any samples. Study 3 : Inhaled FP and FF had similar systemic bioavailability estimates (12.0% [11.0, 13.2] and 15.0% [12.0, 17.3], respectively), but a differential effect on the HPA axis which was in agreement with the known 1.7-fold higher glucocorticoid receptor-binding affinity of FF versus FP. However, for FP 250 μg BID and FF 100, 200 and 400 μg QD, reduction in serum cortisol was not significantly different from placebo. For higher doses, FP 500 and 1000 μg BID, and FF 800 and 1600 μg QD, changes in serum cortisol concentration relative to placebo were −30%, −70%, −41% and −90%, respectively. Repeat inhaled dosing of FP 1000 μg/day (within the therapeutic dose range) resulted in comparable cortisol suppression to MF in the therapeutic range (30% reduction); whereas for FF this occurred at more than 3-fold above the therapeutic dose range (644 μg/day). Conclusions: Single inhaled and intravenous doses of MF and FP (400 μg) resulted in similar bioavailability and reductions in serum cortisol. Repeat dosing of inhaled MF and FP in the therapeutic range (800 μg/day) resulted in greater systemic exposure for MF, and a 35% reduction in serum cortisol that was 2-fold greater than for FP. The higher glucocorticoid receptor-binding affinity and bioavailability, lower clearance and the presence of active metabolites may contribute to the greater systemic exposure and effect on cortisol for MF. Repeat dosing of inhaled FP and FF resulted in similar systemic bioavailability but differed in terms of the dose required for comparable cortisol suppression to MF in the therapeutic range. Unlike FP and FF, MF has active metabolites that may contribute to its systemic effects, while device/formulation performance differences also exist between MF-containing products. Highlights: PK profiles of FP and FF are similar; MF has active metabolites and lower clearance. Cortisol suppression for FP and FF is mainly related to differences in potency. Higher systemic exposure and cortisol suppression are seen with MF versus FP. FP and FF mono and combo products have matching nominal doses and systemic activity. MF mono and combo products have different nominal doses but same systemic activity.